2010
DOI: 10.1007/s10591-010-9127-1
|View full text |Cite
|
Sign up to set email alerts
|

Common Components of Home-Based Family Therapy Models: The HBFT Partnership in Kansas

Abstract: In this article, we provide an analysis of components shared by varying home-based family therapy (HBFT) practices and evidence-based models. Applying a consistent statewide standard for HBFT presents challenges for the training of therapists from varying disciplines, with different levels of experience, and from diverse agencies. We propose focusing on common components across existing evidence-based models and discuss the trainings developed to integrate those components. We address indications and contraind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Settings are controlled in the sense that potential distractions and safety concerns are predictable (Bowen, ). Furthermore, traditional office‐based settings allow a counsellor to proactively identify safety hazards and create effective contingency plans to maintain session focus and overall safety for all attendees (Bowen & Carson, ; Macchi & O'Conner, ). Sanders and Lehmann () had concluded that if there is flexibility in the therapeutic framework for modifications in the environment from the client, the counsellors should allow for it because the sense of safety and comfort this can create has an impact on the therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Settings are controlled in the sense that potential distractions and safety concerns are predictable (Bowen, ). Furthermore, traditional office‐based settings allow a counsellor to proactively identify safety hazards and create effective contingency plans to maintain session focus and overall safety for all attendees (Bowen & Carson, ; Macchi & O'Conner, ). Sanders and Lehmann () had concluded that if there is flexibility in the therapeutic framework for modifications in the environment from the client, the counsellors should allow for it because the sense of safety and comfort this can create has an impact on the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sanders and Lehmann () had concluded that if there is flexibility in the therapeutic framework for modifications in the environment from the client, the counsellors should allow for it because the sense of safety and comfort this can create has an impact on the therapy. The impending feeling of lack of control over the surroundings while working in an unfamiliar setting can lead to various levels of discomfort to the counsellor (Macchi & O'Conner, ). This brings into question the sense of control over the environment and the process of counselling and to what extent the physical framework compliments both in the client's overall experience of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important, a home-based counselor practices within a setting that is determined by the client or his or her family (Macchi & O'Conner, 2010;Mosier et al, 2001;Stinchfield, 2004). In turn, a home-based counselor may conduct a session in a setting that includes multiple distractions and safety concerns (Gale & Austin, 2003).…”
mentioning
confidence: 99%
“…Home-based counseling was created principally as an alternative to out-of-home placement for at-risk youth (Cortes, 2004;Macchi & O'Conner, 2010;Stinchfield, 2004). It gained wide recognition beginning in the 1990s (Hammond & Czyszczon, 2014), and home-based counseling is currently one of the fastest growing segments of mental health services (American Counseling Association [ACA], 2011; U.S. Bureau of Labor Statistics, 2014).…”
mentioning
confidence: 99%
“…Therapists who do not adequately attend to their own self‐of‐the‐therapist concerns are less likely to provide their clients with quality service (Durtschi & McClellan, ). Furthermore, theoretical descriptions of home‐based therapy have repeatedly suggested that providers engaging in these services face additional demands related to their unique roles and responsibilities (Macchi & O'Conner, ).…”
mentioning
confidence: 99%